Cu, Mn and Co molybdates derived from novel precursors catalyze the oxidative dehydrogenation of propane - Palacio, Luz Amparo (2005)
The activity of various transition metal molybdates in the oxidative dehydrogenation of propane was tested. A series of nine molybdates of Zn, Cu, Co, Fe and Mn were synthesized by either a hydrothermal or a precursor method. The catalysts were characterized by X-ray diffraction (XRD), atomic absorption (AA), laser Raman spectroscopy (LRS), and scanning electron microscopy (SEM). The reaction was carried out at atmospheric pressure in a temperature range of 400-600 °C. The copper, cobalt and manganese molybdates were the best performing catalysts. The latter one reached selectivities around 50% at 20% conversion. All the catalysts kept the original structure after reaction. The best and most stable formulation was a cobalt molybdate, the only solid that maintained its surface area after reaction.